Spiritual care - Ommen, Armand Léon van (Theology, 2018)
This article reviews four books on spiritual care in various chaplaincy and counselling settings. Before discussing the books individually, some tensions in the field of spiritual care and chaplaincy are highlighted: the relationship between religion and spirituality, the call for generic caregiving and the demand for tangible outcomes of spiritual care.